Odontogenic Cysts: A 10-Year Retrospective Study in an Iranian Population - Sargolzaei, Soudabeh; Hassanzadeh, Masoud; Eshghyar, Nosratollah; Taghavi, Nasim; Akbarzadeh, Alireza (Journal of Dental School, 2019)
Objectives: The purpose of this study was to determine the frequency of all odontogenic cysts (OCs) along with age range, gender distribution, and the site of involvement over a 10-year period (March 2001 to March 2011) and to compare these data with findings from other surveys. Methods: The archives of departments of oral and maxillofacial pathology from Shahid Beheshti and Tehran University of Medical Sciences were retrieved and analyzed for demographic data such as age, gender, location and histopathological diagnosis of OCs. Results: Of the 8,563 biopsy samples that were received, 1,518 (17.7%) were diagnosed as OCs. Radicular cyst was the most common diagnosis (33.2%), followed by dentigerous cysts (24.1%), and odontogenic keratocysts (18.6%). OC occurred 59.3%, 40.6% in male and female respectively. Mandibular involvement was 62.4% while in maxilla was 37.6%. Conclusion: Our study provided demographic data on a large series in Iran, a Southwest Asian country. In our study, radicular cysts, the most common OC, had a lower frequency compared to that reported in most other studies. On the other hand, calcifying OCs seem to be more prevalent in the Iranian population compared to other populations male to female to female ratio was 1.45:1.